Synthesis of 1,5-Diaryl-3-arylethenyl-2-pyrazolines Under Ultrasound Irradiation - LI*, JI-TAI; ZHAI, XIN-LI; MENG, XIAN-TAO (Asian Journal of Chemistry, 2024)
Synthesis of 1,5-diaryl-3-arylethenyl-2-pyrazolines via the reaction of 1,5-diaryl-1,4-pentadien-3-one and phenylhydrazine in glacial acetic acid was carried out in 32-80 % yields under ultrasound irradiation. This procedure has the advantages of mild conditions, short reaction time and high yield.